THE CAUSAL NEXUS OF FREEDOM OF SPEECH AND HATE SPEECH IN MULTIRACIAL SOCIETY - Khairul Nizam Taib; Mazura Md Sama; Salma Yusof; Noor Azmi M.Z; Zahimi Z.A, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The words that are spoken by an individual are a means through which that person can convey their thoughts and opinions. Nevertheless, as time passes, the complexity of communication increases. Most sovereign constitutions recognize the right to freely express oneself through words as an essential component of the freedom of expression. However, while freedom of speech is one of the most essential international rights, yet it's not absolute. Like all other fundamental rights, it is subject to state-level restrictions. Many people in the age of the internet promote their opinions without recognizing that they are inciting violence against others through hate speech and other forms of online social media. Violence and prejudice against peace and concord may have their origins in disparaging speech. This study through a qualitative method seeks to investigate the scope of freedom of speech, types and effects of hate speech in multiracial society. The aim of the discussion prolongs the validity of having fundamental rights in expressing an individual's thoughts, views, and positively sharing information to achieve the benefits bestowed to society and abusive misinterpreted expression on the same platform. Using the doctrinal analysis, the study shows that freedom of speech is a fundamental right that delicately balanced and cannot be simplified by an objective mechanism. At the outset, it advocates protecting it as long as it doesn't violate other fundamental rights or override them.